Assessing Financial Information System Usability Using System Usability Scale (SUS) and Usability Metric for User Experience-Lite (UMUX-Lite) - Suria, Ozzi (Jurnal Teknologi Sistem Informasi dan Aplikasi, 2024)
The rapid advancement in technology necessitates robust financial information systems (FIS) in educational institutions to manage the increasing complexity and volume of financial transactions. This study evaluates the usability of developed web-based Financial Information System for schools and the Foundation, designed to automate and streamline the management of student tuition fee records. The evaluation employs two prominent usability metrics: the System Usability Scale (SUS) and the Usability Metric for User Experience-Lite (UMUX-Lite). The SUS and UMUX-Lite are tools designed to quantitatively assess a system's usability and user satisfaction. The SUS provides a quick, reliable measure of a product's usability, while UMUX-Lite offers a concise evaluation of user satisfaction with less respondent time without compromising insight quality. Our research methodology included distributing questionnaires to 41 schools, employing SUS and UMUX-Lite questions to gather comprehensive feedback on the FIS's usability. Analysis of the data revealed a SUS score of 77.5, placing the system's usability in the "B+" category, indicative of good user satisfaction. The UMUX-Lite score was slightly higher at 81.69, reflecting excellent usability and aligning with user needs and ease of use. These results affirm the effectiveness of the developed FIS, highlighting its potential to significantly improve financial management processes within schools. The close correlation between SUS and UMUX-Lite scores underscores the system's robustness and intuitive design, suggesting that minor enhancements could further elevate its usability and overall user experience. This study contributes to the field by demonstrating the practical application of SUS and UMUX-Lite in evaluating the usability of financial information systems in educational settings, offering insights for future system enhancements and user-centered design practices.